Glucocorticoids: A Boon or Bane in Dentistry - Subhashree Sahoo (Institute of Medico-legal Publications Pvt Ltd, 2020)
The people who had undergone or are undergoing glucocorticoid therapy present distinctive issues fordental surgeons. The people receiving the steroid therapy have their responses altered to infection and injuryassuage. More importantly, the patients who are taking or have taken glucocorticoids have a possibilityof suffering from acute-adrenal insufficiency when they are introduced to a stressful situation. When apatient with a history of glucocorticoid therapy is under treatment, actual details on the medical history mustbe obtained. The dentist must regulate the requirement for the ensuing preventive measures: a) Systemicantibiotic therapy, b) anxiety control, c) increased administration of glucocorticoids.